Black raspberry restores the expression of the tumor suppressor p120ctn in the oral cavity of mice treated with the carcinogen dibenzo[a,l]pyrene diol epoxide. - Douglas B Stairs (Public Library of Science (PLoS), 2021)
One of the major risk factors for head and neck squamous cell carcinoma (HNSCC) is tobacco smoke exposure, but the mechanisms that can account for disease development remain to be fully defined. Utilizing our HNSCC mouse model, we analyzed oral squamous cell carcinomas (OSCC) induced by the active metabolite of a common smoke constituent, dibenzo[a,l]pyrene diol-epoxide (DBPDE). Analyzing protein expression by either immunofluorescence or immunohistochemistry, we identified biologic processes that are dysregulated in premalignant and invasive cancer lesions induced by DBPDE. Interestingly, p120ctn expression is downregulated in both stages of the disease. In addition to decreased p120ctn expression, there was also increased proliferation (as measured by Ki67), inflammation (as measured by NFkB (p65) expression), neovascularization (as measured by CD31) and recruitment of Ly6G-positive immune cells as well as strong EGFR expression. We also examined the effect of the chemopreventive agent black raspberry (BRB) on p120ctn and EGFR protein expression in DBPDE treated mice. p120ctn, but not EGFR, protein expression increased in mice treated with BRB. Our results suggest that modulation of p120ctn may, in part, account for the mechanism by which BRB inhibits DBPDE induced OSCC in mice.